Penerapan Konseling Kelompok Menggunakan Teknik Breathing Exercises Untuk Mereduksi Kecemasan Sosial Siswa Di SMP Negeri 4 Takengon - Najla, Friantytiara; Syarifah Ainy Rambe; Birrul Walidaini (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Social anxiety (social anxiety disorder) is one of the most common mental health problems experienced by adolescents, particularly in educational settings. This condition is characterized by excessive fear of social interactions, concerns about negative evaluation from others, and physical symptoms such as rapid heartbeat, trembling, and sweating. This study aims to: (1) describe the level of students’ social anxiety before and after the implementation of breathing exercises, and (2) examine the effectiveness of group counseling using breathing exercises in reducing students’ social anxiety.This study employed a Guidance and Counseling Action Research (PTBK) approach conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were students of SMP Negeri 4 Takengon. Data were collected using a Likert-scale questionnaire administered through pre-test, post-test cycle I, and post-test cycle II. The intervention technique used was group counseling with the application of breathing exercises aimed at helping students control their physiological responses to anxiety.The results showed that students’ social anxiety levels before the intervention were in the moderate to high category. After the implementation of the first cycle, the anxiety level decreased to a moderate category. Furthermore, in the second cycle, students’ social anxiety significantly decreased to a low category. This reduction was indicated by the gradual decline in the average anxiety scores across each cycle. In addition, observational results revealed positive behavioral changes, such as increased self-confidence, reduced nervousness when speaking in front of the class, and improved social interaction skills.The findings also demonstrate that group counseling using breathing exercises is effective in reducing students’ social anxiety. This technique helps students achieve relaxation, reduce physical tension, and improve emotional regulation. The group counseling dynamics also provide social support that strengthens behavioral change processes. Therefore, the combination of group counseling and breathing exercises is not only quantitatively effective in reducing anxiety levels but also qualitatively enhances students’ psychological well-being.In conclusion, the implementation of group counseling with breathing exercises is an effective and relevant intervention to help students overcome social anxiety and can be used as an alternative strategy in school guidance and counseling services. Keywords: Group Counseling, Breathing Exercises, Social Anxiety, Junior High School Students, Guidance And Counseling